Plasma treatment on SiO2f/SiO2 composites for their assisted brazing with Nb. (January 2016) - Qi, Jun Lei; Lin, Jing Huang; Guo, Jia Le; Liu, Yu Lin; Cao, Jian; Zhang, Li Xia; Feng, Ji Cai
Abstract: Brazing SiO2f /SiO2 composites with metals is often associated with the problems of poor wettability with active brazing alloy and poor mechanical properties of joints. To overcome these problems, we report the plasma treatment on SiO2f /SiO2 by PECVD for their assisted brazing with Nb. The O–Si–O bonding changed into Si–C bonding on the surface of SiO2f /SiO2 by the plasma treatment can improve the wettability of Ag–Cu–Ti brazing alloy on SiO2f /SiO2 . Furthermore, SiO2f /SiO2 after the plasma treatment can contribute to the infiltration of brazing alloy into SiO2f /SiO2 to form the pinning structure and reducing the residual stress, which could strengthen the joint. The obtained joint has a high shear strength of 60.5 MPa, approximately 11 times higher than that without plasma treatment. Highlights: The O–Si–O bonding changed into Si–C bonding by the plasma treatment can improve the wettability of Ag–Cu–Ti on SiO2f /SiO2 . The plasma treatment can contribute to the infiltration of brazing alloy into SiO2f /SiO2 to strengthen the joint.